The Prospects for Communist China - Rostow, W. W. (London Chapman & Hall, Ltd., 1955)
Studies by several people at the Center for International Studies, Massachusetts Institute of Technology.
Include Index, Appenndix and Bibliography.
Keywords: China -- Communism